CHILDREN'S RESPONSE TO ISLAMIC RELIGIOUS LEARNING AT ERWITA SCHOOL EDUCARE CENTER MEDAN - Masganti Sit; Solihah Titin Sumanti; Fatma Gustina (UIN Sumatera Utara Medan, 2021)
This study aims to analyze children's responses to Islamic religious learning at the ErwitaEducare Center Kindergarten School in Medan, and Islamic learning at the ErwitaEducare Center Kindergarten School Medan.This research uses descriptive narrative qualitative method. To obtain data, researchers conducted observations, interviews and documentation. In analyzing the data, this research was carried out in stages, namely, data collection, data reduction, data presentation and drawing conclusions in obtaining data.The results in this study indicate that the Islamic Religious Learning of this school emphasizes the Learning of Faith, Learning of Worship, and Learning of Morals. the response to Islamic learning shown by the child is to have a positive response or attitude. This can be seen from some of the responses or attitudes of children in learning, namely (a) Responses / attitudes towards the subject matter of Islamic Religion (b) Responses / attitudes of children towards teachers / teachers (c) Responses / attitudes of children in the learning process in Islamic Religious Learning ( d) Cognitive Response (e) Affective Response (f) Conative response. The child shows a positive and responsive response in learning Islamic religion given by the teacher.